Effective Human Capital Management as a Growth Factor in the Agricultural Production Sector - BULKHAIROVA, Zhanna Serikovna; NURTAYEVA, Zhanara Shansharovna; IMASHOVA, Zhulduz Davitovna; SAIMAGAMBETOVA, Gaukhar Amangeldievna; ABDIYEVA, Sayassat Rahmetovna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).05, 2018)
In the present research, the authors consider theoretical and practical aspects of effective human capital management as a growth factor in agricultural production. In the current highly competitive environment, rational and effective management of human capital can improve the performance indicators of the company and thus generate growth in its production. The problems of the formation and development of human capital have been analyzed by both domestic and foreign scientists; however, there are numerous problems that must be addressed, especially in agriculture. Considering special characteristics of agricultural enterprises, the authors attempted to solve these problems by optimizing the structure of human capital, proposed the procedure, made calculations according to this procedure and assessed the obtained results; conducted SWOT analysis of the human capital management in agricultural enterprises and drew the conclusions in the end of the article.